2010
DOI: 10.1177/194008291000300403
|View full text |Cite
|
Sign up to set email alerts
|

Bird Abundances in Primary and Secondary Growths in Papua New Guinea: A Preliminary Assessment

Abstract: Papua New Guinea is the third largest remaining area of tropical forest after the Amazon and Congo basins. However, the growing intensity of large-scale slash-and-burn agriculture and logging call for conservation research to assess how local people´s traditional land-use practices result in conservation of local biodiversity, of which a species-rich and diverse component is the avian community. With this in mind, I conducted a preliminary survey of birds in small-scale secondary plots and in adjacent primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…A repeated survey of rainforest birds was carried out along an elevation gradient on the slopes of Mt. Wilhelm in the Central Range of Papua New Guinea [ 29 , 30 ]. The study was completed along a 30 km long transect with eight sites, spanning from lowland floodplains at 200 m to the timberline at 3700 m. The sampling method was individual counts, which comprised surveying the bird communities at each site by point counts, mist-netting and random walks through the area.…”
Section: Methodsmentioning
confidence: 99%
“…A repeated survey of rainforest birds was carried out along an elevation gradient on the slopes of Mt. Wilhelm in the Central Range of Papua New Guinea [ 29 , 30 ]. The study was completed along a 30 km long transect with eight sites, spanning from lowland floodplains at 200 m to the timberline at 3700 m. The sampling method was individual counts, which comprised surveying the bird communities at each site by point counts, mist-netting and random walks through the area.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study of bird diets in Papua New Guinea showed that 61 of 98 bird species fed on ants, 47 species included ant eggs in their diet, 63 bird species fed on Lepidoptera larvae, and 39 bird species fed on adult Lepidoptera (Tvardikova 2013). Therefore, we identified butterflies and ants as important prey for birds (besides beetles and spiders).…”
Section: Methodsmentioning
confidence: 92%
“…Previous work in primary and secondary forests in Papua New Guinea (Tvardikova 2010) has demonstrated that lowland insectivorous birds and canopy frugivores are particularly sensitive to forest disturbance. Other investigators have also reported that large frugivorous and understory insectivorous birds are sensitive to habitat alteration (Stouffer and Bierregaard 1995, Sekercioglu 2002, Sekercioglu et al 2002, Kattan et al 2004, Lees and Peres 2010.…”
Section: Resumen El Efecto De La Fragmentación Del Bosque Sobre La Rmentioning
confidence: 99%
“…Studies comparing avian species richness and community structure in SF and PF report inconsistent results. Some studies have found equivalent or higher species richness in SF compared to PF (Andrade & Rubio‐Torgler, ; Blake & Loiselle, ; Borges, ; O'Dea & Whittaker, ; Schulze & Waltert, ), while other studies report reduced species richness in SF (Barlow, Mestre et al., ; Bowman, Woinarski, Sands, Wells, & McShane, ; Gibson et al., ; Terborgh & Weske, ; Tvardíková, ). These conflicting results may stem from three key factors: the age of SF studied, the landscape context, and the responses of different avian groups to habitat change.…”
Section: Introductionmentioning
confidence: 99%
“…Studies focusing on young SF may therefore underestimate the longer‐term value of SF for bird conservation. While estimates of avian species richness in young SF are often inflated by non‐forest species, species composition in young tropical SF tends to differ from PF (Barlow, Gardner et al., ; Borges, ; Tvardíková, ). With increasing time since abandonment, both forest structure and bird communities become more similar to those of PF (Andrade & Rubio‐Torgler, ; Borges, ; Raman, ).…”
Section: Introductionmentioning
confidence: 99%